A Cognitive Neuropsychological and Psychophysiological Investigation of a Patient Who Exhibited an Acute Exacerbated Behavioural Response during Innocuous Somatosensory Stimulation and Movement - N. M. J. Edelstyn; S. R. Baker; S. J. Ellis; P. Jenkinson (Behavioural Neurology)
We report findings from a cognitive neuropsychological and psychophysiological investigation of a patient who displayed an exacerbated acute emotional expression during movement, innocuous, and aversive somatosensory stimulation. The condition developed in the context of non-specific white matter ischaemia along with abnormalities in the cortical white matter of the left anterior parietal lobe, and subcortical white matter of the left Sylvian cortex.